The Returns to Education at Community Colleges: New Evidence from the Education Longitudinal Survey - Dave E. Marcotte (Institute for the Study of Labor (IZA), 2016)
Community colleges have long been recognized for their potential in providing access to post-secondary education for students of limited means. Indeed, the recent #FreeTuition movement is built on community colleges as a cornerstone. Previous research on the value of community colleges in shaping earnings and career outcomes suggests that encouraging access to community college is a good investment. But, the evidence base on this issue is limited. The main limitations stem from the fact that what we know comes from data collected from cohorts of students who studied in community colleges more than twenty years ago. In the meantime, the market for higher education has changed drastically, and the Great Recession and economy of the early 21st Century have reshaped how young Americans are educated and begin their careers. For these reasons, I update the evidence on the employment and earnings effects of community college education. I study the experiences of the Educational Longitudinal Survey (ELS) cohort, which graduated from high school and began studying in community colleges at the start of the Great Recession, and who began their working careers in the years after. The experiences of this cohort are important in their own right, since they provide insight into the experiences of American workers during and after one of the largest economic downturns in modern history. Moreover, this paper will provide insight into the role post-secondary education plays in shaping economic security more generally.
Keywords: I21; I23; I26; 330; education; community college